2009
DOI: 10.1111/j.1524-4741.2009.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses the Paclitaxel-Induced Nuclear Factor-κB in Breast Cancer Cells and Potentiates the Growth Inhibitory Effect of Paclitaxel in a Breast Cancer Nude Mice Model

Abstract: Most anticancer agents activate nuclear factor kappa B (NF-kappaB), which can mediate cell survival, proliferation, and metastasis. Curcumin has been shown to inhibit the growth of various cancer cells, without toxicity to normal cells. The antitumor effects of curcumin could be due in part to the inactivation of NF-kappaB. We hypothesize that blocking NF-kappaB activity may augment paclitaxel cancer chemotherapy. In this study, we investigated whether the inactivation of NF-kappaB by curcumin would enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 24 publications
4
56
0
Order By: Relevance
“…Mechanistic studies showed that the combination decreased the expression of MMP-9 and increased apoptosis in the tumors of treated mice. Interestingly, the dose of paclitaxel was much lower (7 mg/kg) than previously reported as a single treatment (Kang et al, 2009). Success has also been shown using in vitro combination studies.…”
Section: Combination Studiesmentioning
confidence: 72%
“…Mechanistic studies showed that the combination decreased the expression of MMP-9 and increased apoptosis in the tumors of treated mice. Interestingly, the dose of paclitaxel was much lower (7 mg/kg) than previously reported as a single treatment (Kang et al, 2009). Success has also been shown using in vitro combination studies.…”
Section: Combination Studiesmentioning
confidence: 72%
“…Yang et al (25) previously demonstrated that luteolin could enhance PTX-induced apoptosis in MDA-MB-231 human breast cancer cells, by blocking signal transducer and activator of transcription 3. Hossein et al (19) showed that PectaSol-C modified citrus pectin could sensitize ovarian cancer cells to PTX by inducing apoptosis, which may lead to an accumulation of cells in the subG 1 and G 1 phases, and cleavage of caspase-3 (24)(25)(26)(27). Numerous studies have reported that CZEO is a promising antitumor drug, which has a direct cytotoxic effect that inhibits tumor cell growth and proliferation, disrupts nuclear metabolism, inhibits angiogenesis and impairs the membrane potential, all of which can be lethal to cancer cells (3,15,28).…”
Section: Discussionmentioning
confidence: 99%
“…the cellular processes controlling synergy or antagonism between cancer therapeutic agents used in combination are currently the subject of intense investigation (2,(22)(23)(24)(25). As many cancers do not fully respond to single-agent treatment, the development of a combination therapy utilizing two common and potent chemotherapeutics such as ptX and a topo I inhibitor holds enormous potential for the treatment of several malignancies.…”
Section: Discussionmentioning
confidence: 99%